Desenvolvimento de objeto pedagógico para o ensino produtivo de gramática : a balança das relações sociais - Paes, Jilcicleide Augusta (2019)
Sociolinguistic studies show that language is heterogeneous and subject to variation, with time, space and social profile. Because of these variations, the linguistic prejudice emerges, which contributes to social exclusion. The school has the task of recognizing the linguistic register in use in a community, respecting diversity, without incurring linguistic prejudice. An example of this diversity is the variation in second person personal pronouns, with the "you / you" variants. Observing the pronominal paradigm of Brazilian Portuguese, according to the descriptive studies based on the use and tradition of normative grammar, we find that the pronouns "tu" and "you" are not adequately portrayed in the didactic materials of Portuguese language, and the character of personal pronoun "you" and the variation in verbal agreement with the pronoun "you". From the perspective of variationist sociolinguistics, in the light of the knowledge acquired in PROFLETRAS, we seek to contribute to the teaching of grammar and new ways of approaching second-person variation in personal pronouns in Portuguese, in the 7th grade A class at Jacintho de Figueiredo Martins, in Aracaju / SE, considering morphosyntactic and pragmatic aspects. Based on descriptive observational research and methodological assumptions of the theory of Linguistic Variation, we initially conducted a study on students' perception of variation in second-person personal pronouns, based on speech and writing situations, considering social and pragmatic aspects. From a data collection instrument to verify the appropriateness of pronoun choices, and from individual interviews with students, we developed the prototype of a didactic-pedagogical resource, along with a teacher's use manual, to support teaching of personal pronouns, considering the variation "you / you" and the semantics of power and solidarity present in the use of pronouns. The didactic resource includes the three axes for grammar teaching proposed by Vieira (2017a) and was tested initially in the research pilot class (7th grade A), then in the 6th, 8th and 9th grade classes, and also in a group of expert judges. After analysis, we concluded that the resource was efficient in its purpose: enable the exploration of the linguistic phenomenon studied, actively involve students in the learning process and contribute to the teacher's work.